Basal Cell Carcinoma of The Skin Diagnostic Challenges: A Case Report - Said Abdul Hadi; Sarip @ Maarof Maisarah Hanim; Lim Sin Siuew (Asian Journal of Medicine & Health Sciences, 2024)
Basal cell carcinoma (BCC) is the most prevalent skin cancer, with the reported incidence within the country remaining relatively low. This trend may lead to instances where the condition is underestimated, particularly when skin lesions persist over an extended period. Consequently, there is a risk of overlooking the potential for malignant transformation of chronic non-healing ulcers, especially as the emphasis often shifts to treating skin infections, a common complication in patients with comorbid conditions such as diabetes mellitus, which itself is a risk factor for delayed wound healing. Although squamous cell carcinoma (SCC) is the most frequent malignant transformation arising from chronic wounds, this case report highlights BCC as a possibility. We also emphasise the importance of early referral as opposed to delayed intervention, as timely management can significantly impact patient's functional and cosmetic outcomes as well as their psychological well-being and that of their family members.